Helminth Parasites of Wildlife in Emilia-Romagna Region - Fiocchi, Alfredo <1982> (Alma Mater Studiorum - Università di Bologna, 2017)
The first chapter of this thesis is a survey on the helminthic fauna of 60 wild canids, 57 red foxes (Vulpes vulpes) and three wolves (Canis lupus italicus), collected in Modena and Bologna provinces, Emilia-Romagna region, Italy. The study focused mainly on the gastrointestinal and hepatic helminths. In total, 15 helminth species were identified, two trematodes, seven cestodes and six nematodes. Our study shows that foxes are reservoir hosts of potential zoonotic parasites, including A. alata, a rare digenean trematode in the Italian paeninsula. In the second chapter we present a research on E. granulosus in red foxes from Eastern Emilia-Romagna. Despite not succeeding in isolating the parasite from the intestines analysed, we identified 16 helminth species among which the trematodes Alaria alata and Phagicola sp., the cestode Joyeuxiella sp. and the nematode Molineus legerae, all representing rare helminth species in the Emilia-Romagna region. The third chapter consists of a deeper analysis of the discovery of the trematode Alaria alata in our region. In the fourth chapter we present a research on respiratory helminths of 90 red foxes from Eastern Emilia-Romagna. Three nematode species were described, namely Eucoleus aerophilus, Filarioides hirthi and Crenosoma vulpis. The fifth chapter is a parasitological survey on the helminthic fauna of 67 diurnal and nocturnal birds of prey. The helminth community was richer in falconiform and accipitriform than in strigiform birds. In particular A.nisus and B. buteo showed the highest number of parasite species. The sixth chapter is a study on gastro-intestinal nematode parasitic infection in adult cattle (dairy and brood cows) bred in Italy. The survey was performed collecting 427 fecal samples from a bovine slaughterhouse in the province of Bologna. One hundred abomasa were also examined to assess the presence of worm burdens.